Equisetum arvense Inhibits Alveolar Bone Destruction in a Rat Model with Lipopolysaccharide (LPS)-Induced Periodontitis - Fumie Shiba; Hisako Furusho; Takashi Takata; Rika Shimizu; Mutsumi Miyauchi (International Journal of Dentistry)
Background and Aims. Equisetum arvense extract (EA) exerts various biological effects, including anti-inflammatory activity. The effect of EA on alveolar bone destruction has not been reported; therefore, we aimed to determine whether EA could inhibit alveolar bone destruction associated with periodontitis in a rat model in which periodontitis was induced using lipopolysaccharide from Escherichia coli (E. coli-LPS). Methods. Physiological saline or E. coli-LPS or E. coli-LPS/EA mixture was topically administered into the gingival sulcus of the upper molar region of the rats. After 3 days, periodontal tissues of the molar region were collected. Immunohistochemistry was performed for cathepsin K, receptor activator of NF-κB ligand (RANKL), and osteoprotegerin (OPG). The cathepsin K-positive osteoclasts along the alveolar bone margin were counted. EA effects on the expression of the factors regulating osteoclastogenesis in osteoblasts with E. coli-LPS-stimulation were also examined in vitro. Results. Treatment with EA significantly reduced the number of osteoclasts by decreasing the RANKL-expression and increasing OPG-expression in the periodontal ligament in the treatment group compared to the E. coli-LPS group. The in vitro study showed that the upregulation of p-IκB kinase α and β (p-IKKα/β), p-NF-κB p65, TNF-α, interleukin-6, and RANKL and downregulation of semaphorin 3A (Sema3A), β-catenin, and OPG in the osteoblasts with E. coli-LPS-stimulation improved with EA-treatment. Conclusion. These findings demonstrated that topical EA suppressed alveolar bone resorption in the rat model with E. coli-LPS-induced periodontitis by maintaining a balance in RANKL/OPG ratio via the pathways of NF-κB, Wnt/β-catenin, and Sema3A/Neuropilin-1. Therefore, EA possesses the potential to prevent bone destruction through inhibiting osteoclastogenesis attributed to cytokine burst under plaque accumulation.